Organizational Culture and Leadership Style Among Local Government Unit of Davao del Norte, Philippines - Jemar B. Abenoja; Dhamian John C. Blase; Ronald E. Almagro (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2024)
This study investigates the relationship between organizational culture and leadership styles among Local Government Unit (LGU) departments in Santo Tomas, Davao Del Norte. A descriptive correlational research design was employed, with data collected from 108 department head employees using a sample size calculator. The organizational culture questionnaire was adapted from Dawson et al. (2011), while the leadership style questionnaire was derived from Marx et al. (2015). Respondents completed the questionnaires personally distributed and collected by the researchers. The findings revealed a mean score of 4.45 (very high) for organizational culture and 4.51 (very high) for leadership style. A significant positive correlation was identified between organizational culture and leadership styles (r = 0.573, p = 0.001), indicating that higher levels of organizational culture are associated with enhanced leadership styles. These results highlight the crucial role of organizational culture in shaping leadership behaviors within LGU departments. The implications of these findings are discussed about organizational development and leadership practices in public administration.